(untitled) (Physical Education, Health and Social Sciences, 2024)
Foreign Direct Investment (FDI) is instrumental in bringing the required capital for economic stability and growth, especially to developing nations such as Pakistan. With Pakistan’s quest for financial stability, FDI is an important source of investment into priority sectors, helping in the formation of capital, generation of employment, exports, and manufacturing. Nevertheless, the nation has faced difficulty in maintaining steady FDI inflows owing to several economic issues. The present research assesses the determinants of FDI inflows in Pakistan with data stretching from 1988 to 2012 by employing Multiple Linear Regression. But in this research, the research will employ a survey method to gather primary data from 200 respondents. The respondents will be professionals, policymakers, economists, business executives, and academicians who have expertise in FDI and economic development in Pakistan. According to the results, financing needs, income, and exports have positive effects on FDI inflows, while internal debt and foreign debt have negative effects on FDI inflows. The study further identifies that foreign investment in Pakistan has persisted in being focused in individual subsectors with less attention on machinery and intermediate goods. In spite of the favorable effects of FDI on GDP growth, employment generation, technology transfer, and market competition, difficulties in the form of corruption, poor infrastructure, and regulatory issues restrict Pakistan’s potential to draw larger volumes of investment. The research emphasizes that Pakistan needs to ensure a sound economic environment and enact investor-friendly policies to attract increased FDI flows. Major recommendations are enhancing governance to fight corruption, enhancing infrastructure, streamlining regulations, and providing tax holidays for foreign investors. Furthermore, targeting FDI towards high-potential sectors like manufacturing, technology, and alternative energy will further drive economic development. By overcoming current challenges, Pakistan can achieve maximum gains from FDI, leading to long-term economic stability and sustainable development. FDI plays a vital role in supplying capital necessary Required for economic growth and stability.